Resource Consumption and Waste Production of the EDEN ISS Space Greenhouse Analogue during the 2018 Experiment Phase in Antarctica - Zeidler, Conrad; Vrakking, Vincent; Zabel, Paul; Bamsey, Matthew; Schubert, Daniel (2020)
EDEN ISS is a European project focused on advancing bio-regenerative life support systems, in particular plant cultivation in space. A mobile test facility was designed and built between March 2015 and October 2017. The facility incorporates a Service Section which houses several subsystems necessary for plant cultivation and the Future Exploration Greenhouse. The latter is built similar to a future space greenhouse and provides a fully controlled environment for plant cultivation. The facility was setup in Antarctica in January 2018 and successfully operated between February and November of the same year. During this approximately nine month period, 268 kg of fresh edible biomass was produced. The cultivation of crops requires a number of resources like water, nutrients and carbon dioxide, but also consumables such as cleaning agents, gloves and towels. The facility also produces waste in various forms such as waste water from cleaning, paper and plastic. In this paper the solid and liquid waste is compared with the resources needed for optimal crop growth on the approximately 12.5 m² of cultivation area inside the EDEN ISS facility. In total, approximately 18 kg of mineral salts were required to prepare the nutrient solution over this initial experimental period. In addition, more than 2,500 liters of reverse osmosis water was supplied to the facility over this period. The consumable waste from the bins inside the EDEN ISS facility consisted of around 9 kg of dry paper and 5 kg of plastic waste.